Crohn’s disease being caused by chronic inflammation of the digestive tract - Wawryniuk, Agnieszka; Rybak, Marzena; Szwajkosz, Katarzyna; Sawicka, Katarzyna; Krzyżanowska, Ewa; Łuczyk, Robert; Szymczuk, Ewa; Tomaszewski, Andrzej (Journal of Education, Health and Sport, 2017)
The incidence of the Crohn’sdiseaseischaracterized by gaogeaficdifferentiation.The incidence rate for the Crohn’sdisease in Western and Northern European countries is estimated at five cases per hundred thousand inhabitants, the morbidity rate is forty to fifty cases per hundred thousand inhabitants. The Crohn’sdisease can be revealed at any age but most often affects young people between the ages of 40 and 50. The Crohn’s is chronic inflammation of digestive tract, which may affect every section of the digestive tract. The characteristic feature of the disease is the phase passage, alternate occurrence of remissions and exacerbations. Inflammatory lesions are most often located in various sections of the gastrointestinal tract. The disease process causes a number of ailments that impair the functioning of the patient